Simira robusta (Rubiaceae, Condamineeae), a new species from the Atlantic Rainforest of south-eastern Brazil - Margalho, Luciano Ferreira; Siqueira, Geovane De Souza; Delprete, Piero G.; Groppo, Milton (Phytotaxa, 2017)
Simira robusta (Rubiaceae), a new species from the Atlantic Rainforest of the Espírito Santo state, south-eastern Brazil, is here described and illustrated, and compared with similar species. It most resembles S. grazielae, from which it differs by the larger inflorescences, antrorse pubescent flowers and fruits, and by its larger fruits. Its habitat and conservation status are discussed. A key to the species of Simira from Espírito Santo state is provided.